A Regional Survey to Determine Factors Influencing Patient Choices in Selecting a Particular Emergency Department for Care. (13th January 2013) - Grafstein, Eric; Wilson, Danielle; Stenstrom, Rob; Jones, Catherine; Tolson, Margreth; Poureslami, Iraj; Scheuermeyer, Frank Xavier; Gaddis, Gary
Abstract Objectives Increases in regional emergency department (ED) efficiencies might be obtained by shifting patients to less crowded EDs. The authors sought to determine factors associated with a patient's decision to choose a specific regional ED. Based on prior focus group discussions with volunteers, the hypothesis was that distance to a specific ED and perceived ED wait times would be important. Methods A cross‐sectional survey was developed using qualitative focus group methodology. The resulting survey was composed of 17 questions relating to patient decisions in choosing a specific ED and was administered in each of six EDs in a single urban Canadian health region at all hours of the day. Ambulatory patients with a Canadian Triage and Acuity Scale (CTAS) level 3 to 5 and aged ≥19 years were surveyed. The primary outcome was the proportion of patients whose main motivation for attending a specific ED was either distance traveled to reach the ED or perceived ED waiting time. Multivariable logistic regression was performed to assess factors influencing both of these reasons. Results A total of 757 patients were approached and 634 surveys (83.8%) were completed. Distance from the ED (named by 44.0% of respondents as their primary reason) and perceived ED wait times (9.3%) were the main motivations for patients to attend a specific ED. Multivariable analysis of factors associated with choosing distance revealed that ED distance < 10 km (adjusted odds ratio [OR] = 2.20, 95% confidence interval [CI] = 1.45 to 3.33; p = 0.001) and age ≥ 60 years (adjusted OR = 1.58, 95% CI = 1.12 to 2.26; p = 0.04) were significant in choosing a particular ED. Multivariable analysis of factors influencing wait times demonstrated that having a painful complaint (adjusted OR = 1.42, 95% CI = 1.05 to 1.98; p = 0.047) and age < 60 years (OR = 1.47, 95% CI = 1.02 to 2.14; p = 0.049) were significant in choosing a particular ED. Conclusions In a multicenter survey of patients from an urban health region, distance to a specific ED and perceived ED wait times were the most important reasons for choosing that ED. Younger patients and those with painful conditions appear to place greater priority on wait times.